Fracture characteristics of a cement concrete pavement plate considering subgrade modulus decay based on a meshless finite block method - Wei, Hui; Zhou, Yu; Huang, Wang; Wen, Pihua; Li, Jue (Frontiers in Materials, 2023)
The decrease of subgrade modulus immersed by rainwater can increase the fracture risk of cement concrete pavement plate significantly. The aim of this study is to develop the meshless finite block method (MFBM) to reveal the failure mechanism of cement concrete pavement due to the weakening of subgrade modulus. A normal distribution function was adopted in this study to represent the modulus distribution of subgrade at the bottom of the cement concrete pavement plate. The settlement results show that the progressive softening model of soil subgrade is more suitable to represent the subgrade modulus decay. The maximum stress of cement concrete pavement mainly concentrates at 1.05-1.15 m of plate edge. The weak fracture position is influenced by the subgrade modulus reduction, the size of the immersion range and the pavement and subgrade thickness. While improving the subgrade modulus, adding plate thickness appropriately can effectively control the cracking of cement concrete pavement. Compared with the finite element model, it is proved that the proposed MFBM has an advantage in the solution of pavement fracture with high accuracy and a few compute time. In addition, findings in this study may provide an evidence for understanding the effect of subgrade modulus on the durable pavement design.